Helpful mobile application for taking care of your pets / Nurul Shahirah Hamdan - Hamdan, Nurul Shahirah (Faculty of Art and Design, 2015)
In this modernization of the technological era, mobile application has become one of the learning medium that has been growing faster in Malaysia. Mobile application is an approach towards the knowledge and skills of the mobile technology. This thesis summarizes a series of investigations into how Mobile application can be designed to promote the learning on how to taking care of your pets. The 'design experiment' methodology was adopted for the study, incorporating different methods of data collection and iterated cycles of design, evaluation, and redesign. Recently much research has been conducted on learning with mobile application, usually from a cognitive people perspective. Principles of design developed in this way have not often been tested in naturalistic settings, however. Therefore in one preliminary investigation students' perceptions of a popular mobile application were investigated. Opinions aligned well with most principles though areas for further research were identified. In order to understand the challenges and opportunities presented on taking care pets, a survey on the topic of helpful mobile application on how taking care your pets was undertaken. The perception of using mobile application might not have realized that you can keep track of everything pet-related on your smartphone is an important area of research in the study of on how to taking care your pets. The objective of this thesis is to define the capacity of knowledge about pets, to study the needs of knowledge about pets among owner and to study about the effectiveness of pet application toward the owners. This research also examines a sample of attitudes toward some important issues with pet keeping, from what constitutes responsible pet guardianship to modern issues in animal welfare. Thirty participants were recruited, and data was collected through individual quantitative questionnaire. Data analysis shows the level of user that agree if helpful mobile application on how taking care pets were provided.